Familial dysbetalipoproteinemia: an underdiagnosed lipid disorder. Issue 2 (April 2017) - Koopal, Charlotte; Marais, A. David; Visseren, Frank L.J.
Abstract : Purpose of review: To review pathophysiological, epidemiological and clinical aspects of familial dysbetalipoproteinemia; a model disease for remnant metabolism and remnant-associated cardiovascular risk. Recent findings: Familial dysbetalipoproteinemia is characterized by remnant accumulation caused by impaired remnant clearance, and premature cardiovascular disease. Most familial dysbetalipoproteinemia patients are homozygous for apolipoprotein ε2, which is associated with decreased binding of apolipoprotein E to the LDL receptor. Although familial dysbetalipoproteinemia is an autosomal recessive disease in most cases, 10% is caused by autosomal dominant mutations. Of people with an ε2ε2 genotype 15% develops familial dysbetalipoproteinemia, which is associated with secondary risk factors, such as obesity and insulin resistance, that inhibit remnant clearance by degradation of the heparan sulfate proteoglycan receptor. The prevalence of familial dysbetalipoproteinemia ranges from 0.12 to 0.40% depending on the definition used. Clinical characteristics of familial dysbetalipoproteinemia are xanthomas and mixed hyperlipidemia (high total cholesterol and triglycerides); the primary lipid treatment goal in familial dysbetalipoproteinemia is non-HDL-cholesterol; and treatment consists of dietary therapy and treatment with statin and fibrate combination. Summary: Familial dysbetalipoproteinemia is a relatively common, though often not diagnosed, lipid disorder characterized by mixed hyperlipidemia, remnant accumulation and premature cardiovascular disease, which should be treated with dietary therapy and statin and fibrate combination.